Combination of Clptm1L and TMEM207 Expression as a Robust Prognostic Marker in Oral Squamous Cell Carcinoma - Hano, Kimika; Hatano, Kiichi; Saigo, Chiemi; Kito, Yusuke; Shibata, Toshiyuki; Takeuchi, Tamotsu (Frontiers in Oral Health, 2021)
Overexpression of Cleft Lip and Palate Transmembrane 1-Like (Clptm1L) confers cancer cell survival through the endoplasmic reticulum (ER) stress survival signaling pathway, while TMEM207 impairs the tumor suppressor function of WW domain containing oxidoreductase (WWOX), which sensitizes cancer cells to ER stress-induced apoptosis. In the present study, we examined whether these two ER stress-related proteins, Clptm1L and TMEM207, could be prognostic markers in oral squamous cell carcinoma (OSCC). Immunohistochemical staining using specific antibodies to Clptm1L or TMEM207 revealed that 31 of 89 tissue specimens exhibited concomitant expression of Clptm1L and TMEM207 at the cancer invasion front. A Kaplan–Meier plot of the patient survival curve followed by a log-rank test revealed that the coexpression of Clptm1L and TMEM207 was significantly associated with poor outcome in patients with OSCC (P = 0.00252). Coexpression of Clptm1L and TMEM207 was closely related to lymph node metastasis (P=0.000574). Both univariate and multivariate analyses demonstrated that coexpression of Clptm1L and TMEM207 predicted the poor prognosis of the patients with OSCC. The present study indicated that the double positive Clptm1L and TMEM207 immunoreactivity was closely related to lymph node metastasis with prognostic value in patients with OSCC.